THE INFLUENCE OF HUMAN RESOURCE CAPACITY AND INTER-AGENCY COORDINATION ON THE FAILURE OF SOCIAL ASSISTANCE PROGRAM DISTRIBUTION IN SABU RAIJU REGENCY - Fanyanna Taruna Here Riwu; Riswanda Riswanda; Nursalam Nursalam (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze the influence of human resource capacity and inter-agency coordination on the failure of social assistance program distribution in Sabu Raijua Regency, a region characterized by 3T (underdeveloped, frontier, and outermost). This study used an associative quantitative approach. Data were collected through a structured questionnaire distributed to 22 respondents directly involved in the distribution of social assistance, including government employees, village officials, and program facilitators. Data analysis used descriptive statistics and multiple linear regression. The results showed that human resource capacity and inter-agency coordination, both partially and simultaneously, significantly influenced the failure of social assistance distribution. Although the human resource capacity of program implementers was generally good in terms of procedural understanding and work experience, weaknesses were found in aspects of digital literacy and interpersonal communication skills. Furthermore, inter-agency coordination was still hampered by data synchronization issues, weak two-way communication, and sectoral egos, which resulted in delays and inaccuracies in distribution. This study recommends strengthening human resource capacity through training focused on digital technology and conflict management, as well as the development of an integrated data system to improve inter-agency coordination to ensure more targeted social assistance